A-042 Incongruence Between Self- and Parent- Report Measures of Executive Function on the Behavior Rating Inventory of Executive Function (BRIEF) in Adolescents with Attention Deficit Hyperactivity Disorder. (28th August 2020) - A, Garagozzo; S, Hunter; D, Smith
Abstract: Objective: Research has demonstrated that adolescents with ADHD show executive dysfunction, although they do not always endorse such difficulties. We investigated inter-rater agreement between parent- and self-reported executive function (EF) in adolescents with ADHD, using the BRIEF. We also sought to investigate the relationship between scores on parent and self-report EF measures with performance on objective EF measures. Method: Utilizing a clinical database, we identified 75 participants (13-17 years; Mage = 14.9; 60% male; 27% African American, 63% White, 3% Hispanic, 7% Other) with a diagnosis of ADHD. We examined inter-rater reliability between parent and self-reported factors on the BRIEF. We then examined the association between parent and self-report BRIEF Inhibition scores and the D-KEFS Color Word Interference (CWI) Inhibition trial, and parent and self-report BRIEF Shift scores and the D-KEFS CWI Inhibition/Switching trial and Trails Letter Number Sequencing trial. Results: Significant associations were found between parent and self-ratings on BRIEF Inhibition (ICC = .22; 95% CI = -.24-.50), Shift (ICC = .24; 95% CI = -.21-.52), Emotional Control (ICC = .45, 95% CI = .137-.655), Plan/Organize (ICC = -.143; 95% CI = -.81–28), and Working Memory (ICC = -.193; 95% CI = -.89-.25) subscales. Correlation comparisons were significant for BRIEF self-report Inhibition and CWI Inhibition (r(73) = −.405, p = .000) only. Conclusion: Results support standing findings regarding poor interrater reliability between parent and self-ratings of daily executive functioning in adolescents with ADHD. Self-report was seen to correlate with performance on objective EF tasks. Clinically, these results highlight the need for multidimensional assessment of ADHD in adolescents.